Evaluation of Academic and Career Counselling Information and Its Relation to Students' Educational Orientation - Alexitch, Louise R.; Page, Stewart (Canadian Journal of Counselling and Psychotherapy, 2007)
One hundred and ninety-three participants responded to a questionnaire about the types of academic and career advising they had received from high school guidance counsellors, high school teachers, university guidance counsellors, and university professors. Responses were classified in terms of the content and perceived usefulness of the information received, and were analyzed on the basis of students' gender and scores on the Learning Orientation-Grade Orientation Scale (Eison, Pollio, & Milton, 1986). Generally, students perceived advice from high school and university guidance counsellors to be less useful than advice received from high school teachers and university professors. In addition, students reported receiving more encouragement and support from high school teachers and university professors than from guidance counsellors. Implications of these findings for the relationship between students' characteristics and advising needs are discussed.